(untitled) - Hendricks, Andrea (New York, 2013)
Today’s Developmental Math students enter college needing more than just the math, and this has directly impacted the instructor’s role in the classroom. Instructors have to teach to different learning styles, within multiple teaching environments, and to a student population that is mostly unfamiliar with how to be a successful college student. Authors Andrea Hendricks and Pauline Chow have noticed this growing trend in their combined 30+ years of teaching at their respective community colleges, both in their face-to-face and online courses. As a result, they set out to create course materials that help today’s students not only learn the mathematical concepts but also build life skills for future success
Keywords: Algebra,Đại số